Low grade malignant eccrine spiradenoma of the vulva: case report, review of the literature and discussion about the role of p53 and HPV - Xavier Catteau; Nicky D'haene; Jean-Christophe Noël (BMC, 2020)
Abstract Background Malignant eccrine spiradenoma is one of the rarest sweat-gland tumors. Here, we describe a rare case of low grade malignant eccrine spiradenoma located at the vulva. Case presentation The vulvar lesion was described as a mass measured 3.5 cm and located in the dermis and subcutis with no attachment to the epidermis. The neoplasm was arranged in ragged sheets or solid nodules sometimes with focal necrosis. The tumor cells had hyperchromatism, pleomorphism, and prominent nucleoli with high mitotic index and KI-67 estimated at 70-80%. Conclusions It's only the fifth case of malignant eccrine spiradenoma localized at the vulva. This is the first time that an HPV genotyping was made in this type of lesion with no HPV found while the p16 expression was diffuse. Moreover, it's the first time that a p53 mutation is detected by sequencing in this location.